Evaluating masked hypertension and its relationship to cardiovascular risk factors and target organ damage using 24-hour ambulatory blood pressure monitoring - Tien, Hoang Anh; Vinh, Nguyen Thi Thanh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Aims: To determine the prevalence of MH and its correlation with cardiovascular risk factors and target organ damage in patients at C Hospital, Da Nang. Methods: This study involved 120 participants aged 40 to 70 years who visited C Hospital, Da Nang, between April 2021 and September 2022. The participants were divided into two groups: 60 individuals with cardiovascular risk factors and 60 individuals diagnosed with hypertension. A cross-sectional descriptive methodology was used. Results: The mean values of systolic blood pressure (SBP) and diastolic blood pressure (DBP) upon waking, the percentage of blood pressure (BP) overload, and morning BP surge were significantly higher in the MH group than in the non-MH group (p<0.05). The percentage of non-dipping BP at night was also higher in the MH group, although the difference was not statistically significant (p>0.05). The MH group exhibited higher BP levels and a greater 24-hour BP range than the non-MH group. Patients with obesity, central obesity, dyslipidemia, diabetes, coronary heart disease, and smoking had a higher prevalence of MH than those without these risk factors and comorbidities (p<0.05). A correlation was found between 24-hour SBP and DBP and BMI, blood glucose, cholesterol, triglycerides, and LDL levels. The prevalence of left ventricular hypertrophy on ECG, fundus damage, and kidney damage was significantly higher in the MH group than in the non-MH group. The prognostic value of 24-hour SBP for left ventricular hypertrophy, assessed using the ROC curve, was higher than that of 24-hour DBP. Conversely, the prognostic value of 24-hour DBP for fundus and kidney damage was higher than that of 24-hour SBP. Conclusions: MH is significantly associated with target organ damage. Additionally, 24-hour SBP and DBP levels correlate with BMI, blood glucose, cholesterol, triglycerides, and LDL levels.